Transboundary water rights and conflicts in sub-Saharan Africa: conflict prevention through functional transboundary river basin institution-building in the Southern African Development Community region - Mndzebele, Dumsani (Frontiers in Water, 2025)
Many scholars of conflict and hydropolitics argue that not all cooperation is good, and neither is all conflict bad. Hydro-diplomacy scholarship also presents these two phenomena as co-existent and oftentimes manifest in the same river basin. The ‘water for peace’ discourse of the Southern African Development Community (SADC) is therefore premised on the notion of water as an agent for peace; water presenting opportunities for growth and cooperation. However, can we say that the SADC region is able to truly contain or prevent regional water conflict and that the approaches are systematic and fully understood, especially in relation to the issue of water rights and equity of sharing and utilisation of the resource? Furthermore, while various scholars of hydropolitics have somewhat analysed practices of transboundary water cooperation in the region’s river basins, little has been discussed about the form and centre of everything—the SADC process—why and how SADC drives regional water cooperation. This study presents an analysis of regional experience in SADC, to spotlight how the regional body has used water institution-building to advance peace and cooperation between states. Using a qualitative case study approach, the study explores the application of the concepts of transboundary water governance, institution-building, and strengthening in the SADC. The study finds that the SADC approach generates regionally endorsed legal and policy frameworks to drive institution-building and empowerment. The study also finds that the practices promoted by SADC for transboundary water cooperation to achieving this goal include: (a) fostering closer cooperation, including strengthening of good neighbourliness among riparian states; (b) strengthening source-to-sea and source-to-sink cooperation; (c) increasing information sharing and exchanges between River Basin Organisations (RBOs), the new learning from the old; (d) increased establishment and capacitation of new RBO institutions; and others. Except for a very few known cases, the region has largely been able to curb conflicts way upstream before they became a regional concern. For sustained peace through good water cooperation, the study recommends increased development of water diplomacy instruments and the design of inclusive engagement models for all levels of the SADC-cube (namely regional, river basin, and national levels).